Art based volunteering possibilities : viewpoint of the trainers - Tolga Vuranok, Turan; Ozcan, Mustafa; Miliūnienė, Lina; Radzevičienė, Liuda (Social Welfare: Interdisciplinary Approach, 2012)
The article presents the results based on the research performed according to the EU Grundtvig project Empowering volunteering in socially disadvantaged groups of adult learning (No. LLPGRU-MP-2011_LT-00089) in 5 different European countries and Turkey as well. The role of volunteering is described as a two side activity having infl uence on trainers and volunteers expanding their social experience and knowledge of social inclusion of groups who are at social risk. The results prove that new kind of knowledge and relationship has changed signifi cantly in the process of adult education. Increasing of two side personal motivation in education process has been set up as well.